2021
DOI: 10.3389/fonc.2021.644197
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Curcumin Derivative 1g Induces Mitochondrial and ER-Stress-Dependent Apoptosis in Colon Cancer Cells by Induction of ROS Production

Abstract: Reactive oxygen species (ROS) play an important role in cellular metabolism. Many chemotherapeutic drugs are known to promote apoptosis through the production of ROS. In the present study, the novel curcumin derivative, 1g, was found to inhibit tumor growth in colon cancer cells both in vitro and in vivo. Bioinformatics was used to analyze the differentially expressed mRNAs. The mechanism of this effect was a change in mitochondrial membrane potential caused by 1g that increased its pro-apoptotic activity. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…For example, the inhibition of PERK prevented CHOP10 upregulation and the initiation of apoptosis in colon cancer cells treated with the dihydroartemisinin, NSC735847 [ 40 ]. In a different study, blockade of PERK inhibited apoptosis in colorectal cancer cells exposed to a derivative of the natural compound, curcumin [ 41 ]. Similar to these findings, we report ER stress-mediated apoptosis was propagated through PERK in 15d-PMJ 2 treated cells as the blockade of PERK (GSK2606141) and inactivation of downstream eIF2α (salubrinal) prevented cell death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inhibition of PERK prevented CHOP10 upregulation and the initiation of apoptosis in colon cancer cells treated with the dihydroartemisinin, NSC735847 [ 40 ]. In a different study, blockade of PERK inhibited apoptosis in colorectal cancer cells exposed to a derivative of the natural compound, curcumin [ 41 ]. Similar to these findings, we report ER stress-mediated apoptosis was propagated through PERK in 15d-PMJ 2 treated cells as the blockade of PERK (GSK2606141) and inactivation of downstream eIF2α (salubrinal) prevented cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have been made with curcumin alone and its derivatives. Wang et al (2021) [ 34 ] recently reported one molecule with potential activity in colon cancer cells (HCT116 and HT29), causing changes in mitochondrial membrane potential. In addition, Agarwal and colleagues (2018) [ 35 ] reported that the treatment with curcumin alone induced significant changes in the mitochondrial membrane potential of HT29 cells in a dose- and time-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhang et al [43] reported that libertellenone H treatment significantly increased intracellular ROS generation and induced apoptosis in human pancreatic cancer cells in a ROS-dependent manner. Similarly, curcumin derivatives markedly increased ROS production in colon cancer cells [44]. Furthermore, naringenin-inhibited cell growth was effectively increased through intercellular ROS production [45].…”
Section: Discussionmentioning
confidence: 97%